Implementation of the Creative Economy Curriculum in Economic Education of Islamic Boarding Schools - Almira Keumala Ulfah; Iskandar Iskandar; Trie Nadilla (AL-ISHLAH: Jurnal Pendidikan, 2023)
Indonesia, the world's largest Muslim nation, is developing a sharia economy. Creative economy is essential to Indonesia. This is called Sharia-based in the creative economy. Including a Sharia-based creative economy in public, madrasah, and Islamic boarding school curricula. Islamic boarding schools preach Islam and produce productive workers. The aim of this research is to examine how the application of modern and traditional Dayah curriculum standards can increase Sharia-based creative economic empowerment as well as the inhibiting and supporting factors for Sharia-based creative economic empowerment through the application of modern and traditional Dayah curriculum standards. This research at Sekolah Tinggi Ilmu Tarbiyah. Syamsuddhuha (STIT) (in the Modern Dayah category) and Dayah Raudhatul Ma'Arif Cot Trueng Muara Batu (in the Traditional Dayah category). Participatory Action Research (PAR) method. The two Dayah (Islamic boarding schools, ed.), the implementation of the creative economy curriculum in economic education at Islamic boarding schools has great potential to improve the quality of economic education at Islamic boarding schools. By using a creative and innovative approach, this curriculum can help improve students' skills and understanding of economic concepts and prepare them to face the world of work in the future. However, several inhibiting factors need to be considered in the implementation of the creative economy curriculum, such as the lack of support from the pesantren management and limited resources. Therefore, it takes strong commitment and support from all related parties so that the implementation of the creative economy curriculum can be successful and sustainable.